Impact of Aerobic Training and Probiotic Intervention on Nrf2 and GLUT4 mRNA Levels in Non-Alcoholic Fatty Liver Disease: An Experimental Study in Male Wistar Rats - AliMohammadi, Amin; Gholami, Mandana; Ghazalian, Farshad (Health Nexus, 2025)
Background and Aims: Previous research has explored metabolic regulation improvements and therapeutic potential for treating fatty liver disease through various approaches. This study examines how the Impact of Aerobic Training and Probiotic Intervention on Nrf2 and GLUT4 mRNA Levels in Non-Alcoholic Fatty Liver Disease: An Experimental Study in Male Wistar Rats Methods: We randomly assigned forty male Wistar rats (weighing 220 ± 20g) to five distinct groups: Healthy Control (HC), NAFLD Control (NC), NAFLD with Aerobic Exercise (NAE), NAFLD with Lactobacillus Supplementation (NLS), and NAFLD with combined Aerobic Exercise and Lactobacillus Supplementation (NAELS). The healthy control group maintained a standard diet, while all other groups received oral tetracycline (140 mg/kg body weight dissolved in 2 ml water) through gavage for seven days to establish NAFLD conditions. The six-week intervention protocol included treadmill running at 18 m/min for exercise groups. Probiotic intervention groups received daily L. Rhamnosus GG doses (10⁹ CFU/mL) via gavage for five weeks, administered five days per week. We conducted liver biopsies alongside these interventions and measured Nrf2 and GLUT4 expression in liver tissue using Real-Time PCR. Statistical analysis employed two-way ANOVA with Tukey post hoc tests, establishing significance at p≤0.05. Results: We observed significant differences between the NC and HC groups (p=0.0000) as well as between NC and NAELS groups (p=0.029). The combined intervention group (NAELS) demonstrated the strongest effects on both Nrf2 (η²=0.35) and GLUT4 (η²=0.52) expression levels. These findings indicate that combining aerobic exercise with Lactobacillus supplementation substantially improves both gene expressions compared to individual interventions. Conclusion: Our findings suggest that combining aerobic exercise with Lactobacillus supplementation enhances Nrf2 and GLUT4 expression, potentially contributing to improved metabolic health in NAFLD patients. This combined approach may offer therapeutic advantages over single interventions for managing fatty liver disease.